A Comparison of Centralised and Decentralised Scheduling Methods Using a Simple Benchmark System. Issue 11 (2018) - Tochev, E.; Pfifer, H.; Ratchev, S.
Abstract: This paper is intended to provide a comparison of a centralised scheduling system, a simple Multi-Agent System (MAS), and a Mixed Integer Linear Programming (MILP) formulation. The systems are tested on a simulation of a small scale flexible job shop that has machines in series and in parallel. The performance of the systems is assessed by running a batch of randomized jobs and comparing the number of late jobs and the length of time by which they are delayed. Additionally, simulations with random product failure are included to assess how well the systems perform with disruptions.